Translating web multimodalities: Towards inclusive web localization - Maribel Tercedor Sánchez (Revista Tradumàtica, 2010)
This paper addresses the role of the translator in web localization within the e-inclusion paradigm. We argue that multimodality and forms of accessibility should be offered in an integrated way. Additionally, the aspects that shape the concept of e-inclusion need to be researched from a cognitive and linguistic perspective in the web localization scenarios.